Filsafat Behaviorisme Dalam Pendidikan Anak Usia Dini Perspektif Rudolf Steiner - Zahratur Rahma; Maemonah Maemonah (UIN Sultan Maulana Hasanuddin Banten, 2021)
This article aims to understand the philosophy of Behaviorism in early childhood education from the perspective of Waldorf (Rudolf Steiner) which is applied to its usefulness in the learning process. Steiner is an educational theory commonly referred to as Waldorf, the word